2015
DOI: 10.1177/0194599815580978
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Socioeconomic and Demographic Factors in Patients with Chronic Rhinosinusitis and Allergic Fungal Rhinosinusitis

Abstract: Within our cohort of patients residing in North Carolina, those with CRS have higher income, more access to primary care, and lower markers of disease severity than those with AFRS. These data continue to support the notion that AFRS merits classification as a distinct subtype of CRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 35 publications
5
62
0
Order By: Relevance
“…Social factors that affect access to and utilization of rhinology care are poorly understood, despite the significant health care burden that CRS presents. [1][2][3] It is critical to understand how these social determinants of health affect access to care and disparities in the diagnosis and treatment of CRS. Perceived effectiveness of interventions may differ based on race, educational level, and other social factors.…”
Section: Discussionmentioning
confidence: 99%
“…Social factors that affect access to and utilization of rhinology care are poorly understood, despite the significant health care burden that CRS presents. [1][2][3] It is critical to understand how these social determinants of health affect access to care and disparities in the diagnosis and treatment of CRS. Perceived effectiveness of interventions may differ based on race, educational level, and other social factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States patients with AFRS are more likely to be male and African American and also prone to have more significant bone erosion/ expansion than other patients with CRSwNP, lower per capita income, and less access to health care. [29][30][31][32][33] Host genetics appear to be an important predisposing factor in the development of AFRS, although this is still incompletely defined. It remains speculative as to whether genetic factors can influence immune pathways that could help define AFRS as a distinct endotype of CRSwNP.…”
Section: Host and Environmental Factors For Afrsmentioning
confidence: 99%
“…Several retrospective investigations conducted in the southeastern United States have suggested that AFRS diagnosis is associated with lower socioeconomic status; the same studies have identified AFRS patients as presenting with advanced markers of disease, such as bone erosion and orbitocranial complications. 3 , 11 , 12 Conversely, in a retrospective review of 54 patients with AFRS, Ghegan et al 6 found no link between socioeconomic status and bone erosion in AFRS. Observations regarding the comorbidity of asthma in AFRS subtypes underscore an inherent biologic divergence from other subtypes of CRS.…”
Section: Epidemiology Of Afrsmentioning
confidence: 99%